CHALLENGES OF IMPLEMENTING CLOUD SECURITY SYSTEM THROUGH IDENTITY, ACCESS & RISK MANAGEMENT [IARM] IN A HYBRID IT ENVIRONMENT - Sai Siddhartha Chary Aylapuram, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The majority of promises of cloud security -- improved IT efficiency, flexibility and scalability -- come with one major challenge: security. As enterprise IT adopts more cloud systems while keeping on-premium solutions, controlling who is granted access to which applications becomes increasingly important. This presents CIOs and their teams with a whole new set of identity management challenges. In addition, users must keep track of multiple URLs, user names, and passwords to get access to their applications from the ground to the cloud. Its role is also fundamentally changing. The spread of IT resources in the public sector has been associated with a sharp increase in the level of intra-organizational and inter-organizational communications. Strengthening security can create friction for your employees and consumers. To implement identity management, an enterprise must be able to plan and collaborate across business units. Identity management works best when IT, security, HR, and other departments are involved. Identity management systems must enable companies to automatically manage multiple users in different situations and computing environments in real time. There are challenges in security as a part of Identity, Access & Risk to Verify Trust helps to protect against malicious actors while balancing Multi-Factor Authentication (MFA) requirements